Sensitivity of arterial baroreflex in the terms of body recovery after training load - О. V. Guzii; A. P. Romanchuk (Zaporožskij Medicinskij Žurnal)
The Aim of the work is to determine the changes in baroreflex sensitivity of highly qualified athletes in the recovery period after the training load.